Solute chemistry and arsenic fate in aquifers between the Himalayan foothills and Indian craton (including central Gangetic plain): Influence of geology and geomorphology - Mukherjee, Abhijit; Scanlon, B.; Fryar, A.; Saha, D.; Ghosh, A.; Chowdhuri, S.; Mishra, R. (Pergamon, 2012)
Information on groundwater chemistry in the central Ganges basin can provide insights into recharge, provenance, and fate of solutes in arsenic (As)-affected areas upstream of the more intensively studied Bengal basin. The geological and geomorphological units of the region are much more discernible than the Bengal basin aquifers. Moreover, the region is less affected by groundwater abstraction, which complicates interpretation of As distributions in the Bengal basin. The study area extends from the northern edge of the Indian craton outcrops to the foothills of the Himalayas. Geologic units in the area can be broadly classified as pre-Cenozoic metamorphics and volcanics (PC), older alluvial deposits of the Ganges and its tributaries (OA), younger or active alluvial deposits of the Ganges and its tributaries in the basin (YA), and sediments of the Himalayan foothills (piedmont, PD). Stable-isotopic analyses indicate groundwater in these units has been recharged by meteoric or surface water that has generally undergone some evaporation. The hydrochemical facies is generally a Ca-HCO 3 type. While most of the solutes in the YA groundwater are derived from carbonate dissolution, many of the PD, PC and OA groundwater samples are influenced by silicate weathering, suggesting that leaching of metamorphics and volcanics acts as a major source of solutes. Redox conditions are highly spatially variable (oxic to methanic, dominated by metal reduction), with no systematic depth variation within sampled aquifers. More than 75% of YA and PD groundwater samples have As=0.01mg/L, but As was detected in only one OA sample and no PC samples. Arsenic is probably mobilized by reductive dissolution of Fe-Mn (oxyhydr)oxides in the alluvium, with possibility of competitive anionic mobilization. Hence, relative to the Bengal basin, in addition to lower groundwater abstraction influence, groundwater chemistry in the study area reflects a greater variety of differences in the geological and geomorphological settings of the aquifers. © 2012 Elsevier Ltd.